Implementation of Scientific Approach in Economic Learning - Indriawan, Rois; Slamet, Achmad; Kardoyo, Kardoyo (Journal of Economic Education, 2018)
Based on Permendikbud Number 22 of 2016 regarding the standard of primary and secondary education process, the policy is a motivation to conduct research to know the extent to which the implementation of scientific approach in economic learning. This research aims to find out and analyze the preparation of RPP (Lesson Plan), implementation of learning, evaluation of learning economic and students’ perception to the teacher’s skill in implementing economic learning by using scientific approach. The significance of this research can add to the repertoire of science on the implementation of scientific approach in economic learning. This research uses desciptive qualitative approach. The research technique used to collect the research data in the form of interview, observation, and documentation. The data analysis is done by data reduction, data presentation and conclusion. To obtain valid data used triangulation of data. The result indicates; the preparation of lesson plan is adjusted to the rule or instruction that applies in the school either through meetings or internal MGMP (Teacher Education Consensus Points). The implementation of economic learning is carried out with the system and principle of scientific learning that is student center. Assessment conducted at SMA Negeri 2 Mranggen is authentic consisting of process or skill assessment conducted through observation with assessment indicator of group work, individual work and presentation. According to the students the skill of economics teacher at SMA Negeri 2 Mranggen in economic learning by using scientific approach is good enough.